Science and football: evaluating the influence of science on performance - Drust, B.; Green, M. (Journal of Sports Sciences, 2013)
The scientific study of football has its origins in the early research completed in the 1970`s. Since these early efforts the available scientific knowledge base related to football has developed substantially. The ability of this scientific information to influence practice in the day-to-day activity of football organisations, especially elite teams, has been largely taken for granted. The close examination of this impact can lead to more uncertainty regarding the usefulness of the scientific data to the sport. Few articles are available that have attempted to critique the link between science and football practice. As such, the aims of this article are 2-fold; (i) to examine the historical background to "science and football" and to analyse the influence of sports science research on the current practice of coaches and practitioners within the sport and (ii) to identify potential ways to increase the influence of scientific research on practice in the "real world".